Against a General Theory of Populism: The Case of East-Central Europe - László Andor (Intereconomics, 2020)
Social science, like all other sciences, is supposed to explore the substance below the surface of things. However, populism discourse in general is stuck on the surface, focusing on style, outlook and appearance.
Keywords: 330